2016
DOI: 10.1111/jphd.12162
|View full text |Cite
|
Sign up to set email alerts
|

Does self‐efficacy mediate the effect of oral health literacy on self‐rated oral health in an Indigenous population?

Abstract: Given that SE is a construct amenable to change, our results suggest that interventions that aim to improve SE may have positive impacts on SROH among this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…Individuals who are more educated, have less difficulty in accessing and comprehending dental care instructions for tasks such as daily brushing and flossing. The findings of the study at hand are in agreement with several previous studies[ 20 21 ] while simultaneously being in contrast with Lee et al . in 2012,[ 6 ] who failed to find any significance between dental literacy and PSR-OHS ratings.…”
Section: Discussionsupporting
confidence: 91%
“…Individuals who are more educated, have less difficulty in accessing and comprehending dental care instructions for tasks such as daily brushing and flossing. The findings of the study at hand are in agreement with several previous studies[ 20 21 ] while simultaneously being in contrast with Lee et al . in 2012,[ 6 ] who failed to find any significance between dental literacy and PSR-OHS ratings.…”
Section: Discussionsupporting
confidence: 91%
“…However, some authors revealed that 46% had low health literacy [38]. Among Indian participants, it was found that moderate literacy in 33.1%, lower literacy in 37.6% and adequate literacy in 29.3% of subjects [39] and the health literacy was reported to be poor in a group of Iranians [40].…”
Section: Discussionmentioning
confidence: 99%
“…A range of dental behaviours have been associated with self‐efficacy, such as flossing , brushing of teeth , and use of dental services . Self‐efficacy has also been associated with adherence to periodontal treatment, having a toothbrush , and level of oral health literacy . It has also been shown to be associated with oral health status, including gingival bleeding, periodontal disease, and self‐rated oral health .…”
Section: Discussionmentioning
confidence: 99%